Apoptotic index for prediction of postmolar gestational trophoblastic neoplasia - Braga, Antonio [UNESP]; Maesta, Izildinha [UNESP]; Soares, Renan Rocha [UNESP]; Elias, Kevin M.; Custodio Domingues, Maria Aparecida [UNESP]; Barbisan, Luis Fernando [UNESP]; Berkowitz, Ross S. (Elsevier B.V., 2016)
BACKGROUND: Although 85% of patients with a complete hydatidiform mole achieve spontaneous remission after a few months, 15% of them will experience gestational trophoblastic neoplasia, which requires chemotherapy. To date, there is no biomarker to predict post-molar gestational trophoblastic neoplasia before the initiation of human chorionic gonadotropin surveillance. OBJECTIVE: The purpose of this study was to assess the relationship between the expression of apoptosis markers in the molar villous trophoblasts and the subsequent development of gestational trophoblastic neoplasia after the evacuation of a complete hydatidiform mole. STUDY DESIGN: This was a retrospective cohort study of patients with complete hydatidiform mole who were diagnosed, treated, and followed at the Center of Trophoblastic Diseases (Botucatu/Sao Paulo State and Rio de Janeiro/Rio de Janeiro State, Brazil) from 1995-2014. Patients were divided temporally into derivation (1995-2004) and validation (2005-2014) cohorts. Immunohistochemistry was used to examine tissue expression of the apoptosis inhibitor survivin or the proeapoptotic enzyme caspase-3. Survivin stains for cytoplasmic and nuclear expression were evaluated independently. Caspase-3 expression was measured as an apoptotic index of positive staining cells over negative staining cells multiplied by 100. Receiver operating characteristic curves were then constructed, and the area under the curve was calculated to test the performance characteristics of the staining to predict the subsequent development of gestational trophoblastic neoplasia. RESULTS: The final study population comprised 780 patients, with 390 patients in each temporal cohort: 590 patients entered spontaneous remission, and 190 patients experienced post-molar gestational trophoblastic neoplasia. Neither nuclear nor cytoplasmic survivin expression performed well as a predictor of subsequent gestational trophoblastic neoplasia. The caspase-3 apoptotic index was a strong risk factor for subsequent gestational trophoblastic neoplasia development. When the apoptotic index was < 4%, the risk of gestational trophoblastic neoplasia had an odds ratio of 35.55 (95% confidence interval, 14.02-90.14; P < .0001) in the derivation cohort and an odds ratio of 25.71 (95% confidence interval, 10.13-65.29; P <.0001) in the validation cohort. However, in both cohorts, the positive predictive value for gestational trophoblastic neoplasia of an apoptotic index < 4.0% was modest (49% in the derivation cohort and 41% in the validation cohort); the negative predictive value for gestational trophoblastic neoplasia of an apoptotic index >= 4.0% was high (97% in both cohorts). CONCLUSION: The subsequent development of gestational trophoblastic neoplasia after evacuation of complete hydatidiform mole is tied closely to the apoptotic index, which may be a useful biomarker for future prospective studies.
Keywords: apoptotic index; Brazil; complete hydatidiform mole; gestational trophoblastic neoplasia; receiver operating characteristic; survivin